Taxonomic significance of leaf micromorphology in selected garcinia from peninsular Malaysia - Emlee, Aiesyaa Majdiena; Che Amri, Che Nurul Aini; Midin, Mohd Razik (IIUM Press, 2023)
Garcinia is a notably large genus from Clusiaceae. This genus is approximately discovered across Asia and Africa, predominantly in Southeast Asia. The recent taxonomic revision revealed several changes in the species classification within the Garcinia taxa. Additionally, few data on the anatomical characteristics of Garcinia species in Malaysia have been documented recently. This study aims to identify the leaf micromorphological characters using scanning electron microscopy (SEM) on Garcinia mangostana var. mangostana, G. mangostana var. malaccensis and G. celebica in Peninsular Malaysia. The result of this study found several important characteristics in terms of stomatal size, stomatal shape as well as abaxial and adaxial cuticular sculpturing. In conclusion, this study proposed that the anatomical characteristics in these selected Garcinia species might have a significant taxonomic value that can be applied to species identification and classification.